2014
DOI: 10.1177/0003489414524169
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Recurrence of Squamous Cell Carcinoma Involving the Temporal Bone

Abstract: We have identified multiple factors that are associated with increased recurrence of SCC involving the temporal bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…However, in an 11‐year cohort study, multivariate analysis did not find a robust relationship between large‐caliber PNI and prognosis . Despite these contradictory findings, PNI has been confirmed as a route for invasion of the temporal bone, a rare complication of cutaneous SCC with a poor prognosis . One study reported an incidence of PNI of 84.4% in patients with stages III and IV cutaneous SCC of the auricle who underwent temporal bone resection …”
Section: High‐risk Factors In Cutaneous Squamous Cell Carcinomamentioning
confidence: 98%
See 1 more Smart Citation
“…However, in an 11‐year cohort study, multivariate analysis did not find a robust relationship between large‐caliber PNI and prognosis . Despite these contradictory findings, PNI has been confirmed as a route for invasion of the temporal bone, a rare complication of cutaneous SCC with a poor prognosis . One study reported an incidence of PNI of 84.4% in patients with stages III and IV cutaneous SCC of the auricle who underwent temporal bone resection …”
Section: High‐risk Factors In Cutaneous Squamous Cell Carcinomamentioning
confidence: 98%
“…In particular, these regions show increased metastatic potential to the parotid and cervical lymph nodes . Additionally, cutaneous SCC in the high‐risk periauricular region is particularly associated with locoregional invasion of the temporal bone …”
Section: High‐risk Factors In Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%
“…6,8 Although PFN involvement by lymphatic metastases is documented in the literature, the AFV is not always well dissected in its cranial course, owing to the presence of the marginal mandibular nerve (MMN) in this area, which crosses the vein laterally. 8,9 Iatrogenic injury to the MMN is in fact an aesthetic issue for the patient and a potential cause of medicolegal action. 10 For this reason, in clinical practice, the AFV is often interrupted and ligated, and the cranial portion of the vein is lifted to protect the MMN in a flap consisting of the trunk of the vein and the superficial cervical fascia, which is elevated and reflected superiorly (Hayes Martin maneuver; Figure 2 ).…”
mentioning
confidence: 99%
“…Metastases to PFNs from squamous cell cancer have been reported in 3% of temporal bone cancers, 5.5% of tongue cancers, 7% of head and neck skin cancers, 8% of oropharynx cancers, and 7.5% to 35% of oral cavity primaries. 2,8,12…”
mentioning
confidence: 99%
“…Varying recurrence rates for SCC have been reported based on the site of involvement, metastasis, and grade. In a retrospective study, 30% SCCs involving temporal bone were found to recur within an average of 5.8 months [11]. Others have reported lower SCC recurrence rates of 9–15% [12, 13].…”
Section: Introductionmentioning
confidence: 99%